Artificial Intelligence and Big Data in Digital International Relations - S. V. Shitkov (Проблемы постсоветского пространства)
The article examines the role of artificial intelligence (AI) and big data in the context of digital international relations. It explores the historical stages of AI development, key technological directions such as machine learning and neural networks, and their impact on the  economy, politics, and society. Special attention is paid to the strategic importance of big data as a critical resource for AI advancement, its role in shaping digital sovereignty, and global technological competition. The author investigates contemporary challenges related to the ethical and legal aspects of AI, including regulation, security, and international cooperation. The national strategies of leading countries (USA, China, EU, Russia) in the field of AI are analyzed, focusing on their approaches to ensuring technological leadership and data protection. The article emphasizes the need for universal international norms to prevent the fragmentation of the digital landscape and guarantee equitable access to technologies. The study highlights the transformation of international relations under the influence of AI, where the technological race has become the new “Great Game” of the 21st century. In conclusion, recommendations are provided for establishing a balanced global AI governance system based on multilateralism, fairness, and the consideration of all nations’ interests.